Linking Leader Humor to Employee Innovative Behavior: The Roles of Work Engagement and Supervisor’s Organizational Embodiment - Zhang, Jingjing; Su, Weilin (Frontiers in Psychology, 2020)
The influence of leader humor on employee innovative behavior has been attracting increasing attention from various scholars and enterprises. Based on previous relevant literatures in the fields of humor, leadership and innovation, our study proposes and verifies a model to examine the internal mechanism and boundary condition of the relationship between leader humor, work engagement, supervisor’s organizational embodiment and employee innovative behavior. Specifically, we introduce work engagement as a mediator in the relationship between leader humor and employee innovative behavior, and supervisor’s organizational embodiment as a moderator in the relationship between leader humor and work engagement. Then, we conduct two questionnaires on Chinese employees and their direct supervisors at two different times to collect the sample data. In total, 383 supervisor-subordinate dyads were collected. The results suggest that leader humor can promote employee innovative behavior. Work engagement partly mediates the influence of leader humor on employee innovative behavior. Supervisor’s organizational embodiment of employee positively moderates the influence of leader humor on work engagement, that in turn, ultimately accounts for employee innovative behavior. Through the analyses above, our conclusions not only further verify and develop some previous points on leader humor and employee innovation, but also carry certain management implications for promoting employee innovative behavior from the perspective of leader humor.